Women's comprehensive health care in contemporary Tunisia - Foster, AM (2001)
This dissertation explores the strengths and limitations of national health policy in Tunisia. The achievements of the Tunisian women’s health program, as reflected in both statistical and elite-centered historical analyses, include anv expansive health infrastructure, near universal primary health care coverage, and pioneering reproductive health initiatives. Yet the dominant historical narrative divorces women’s health from the broader social, economic, and political context and largely excludes the experiences and perspectives of women from its analysis. Furthermore, research dedicated to women’s health has historically concentrated almost exclusively on maternal and reproductive health, thereby precluding a sophisticated appreciation of other aspects of women’s health and the full ramifications of health policy. This dissertation moves beyond this limited focus and instead incorporates a more comprehensive vision of women’s health into the assessment of national health services. By approaching women’s health as social history, this dissertation explores the contemporary lives, experiences, and needs of women in Tunisia and chronicles the involvement of women, individually and collectively, in the development, evolution, and implementation of the national women’s health program. Highlighting three specific areas of women’s health in Tunisia -traditional health services, domestic violence, and young women’s health and sexuality- this research reveals both lacunae in the national program and arenas for future improvement. To examine the history and development of the women’s health program in Tunisia, identify limitations and strengths of the program, and consider a wide array of women’s health issues, this dissertation combines qualitative and quantitative research methods. Based on fourteen months of fieldwork in Tunisia, this dissertation draws from the fields of medical anthropology, public health, and feminist studies. In using a variety of extractive and participatory techniques, this interdisciplinary approach yields a more complete and nuanced understanding of the history, evolution, and consequences of the Tunisian national women’s health program and offers a framework by which to examine comprehensive women’s health in other parts of the Middle East and North Africa region.